Book Review “Tak Sempurna”, Fahd Djibran, Bondan Prakoso & Fade2Black, Kurniaesa Publishing, Jakarta, ISBN: 978-602-7618-15-2 - Nurrahma, Ashtria (Universitas Negeri Semarang, 2022)
In this novel told about the figure of Rama, one of the high school students who feels that in this school something is wrong. There are a lot of things that shouldn't be in a school. According to rama his school is a trash can and for all the dirt and decay of the world. Rama is said to be almost the same as high school students in general. But from this book we can see and be made aware that many events that are actually inappropriate exist but have become commonplace in school. Starting from students who died from fighting, pregnant out of wedlock because of free sex. Things like this are very unfortunate if it keeps happening. They are the next generation of a nation that should not experience all of them.